Pengaruh Kepemimpinan Dan Komunikasi Terhadap Kinerja Pegawai Aparatur Sipil Negara Pada Dinas Perhubungan Kabupaten Karawang - Dadan Hermansyah; Sonny Hersona GW; Nunung Nurhasanah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Employee performance, especially in government agencies, is one of the most important things to achieve the vision, mission and goals, so various efforts must be made for an institution such as the Karawang Regency Transportation Service in an effort to improve it. This study aims to analyze the influence of leadership and communication on employee performance. This research was conducted at the Karawang District Transportation Office using a sample of 150 employees. Data was collected by conducting interviews and distributing questionnaires. Furthermore, the data that has been collected is analyzed using path analysis. The results of this study indicate that leadership and communication have a moderate and positive relationship. Partially, the influence of leadership on employee performance is 26.2% and the effect of communication on the performance of employees of the Karawang Regency Transportation Service is 23.3%. And simultaneously shows that leadership and communication on the performance of employees of the Karawang Regency Transportation Office are 49.5% and the remaining 50.5% are influenced by other factors not examined. Leadership provides the greatest contribution to the performance of employees of the Karawang District Transportation Office. Keywords: leadership, communication, performance.